Archives Management System in the General Subdivision of the Regional Education Office of North Sulawesi Province - Jetty E. H. Mokat; Goinpeace H. Tumbel; Nanda A. Onibala (Technium Social Sciences Journal, 2023)
This study aims to describe the filling management system in the general sub-section of the regional education office in North Sulawesi Province. This study uses a qualitative approach, with data collection techniques through observation, interviews, and documentation. The data obtained were analyzed by descriptive qualitative. The data source are the head of the General Sub-Division, employees and archive managers in the General Sub-Division at the Regional Education Office of North Sulawesi Province. The research results show that: 1). Archive storage procedures are not in accordance with the standards set in the law. Standard Operating Procedures (SOP) are ignored. To the knowledge of the Head of the existing Service they made everything in a structured way so that it is currently being tested. 2). Human Resources. There is no archivist or someone who has competence in the field of archiving, as a result the archives are not stored properly. 3). Facilities and infrastructure. Facilities and infrastructure as one of the requirements in the filing system/archive storage are inadequate. The existence of abandoned and unkempt facilities and infrastructure causes the management and storage of documents not up to standard. 4). Supervision and Control. Lack of supervision from the leadership makes the filing and storage management system not good, not organized. And the administration of archives is not in accordance with archival rules and standards.